2012
DOI: 10.1590/s0102-86502012000700006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of brain death and associated trauma on solid organ histological characteristics

Abstract: PURPOSE:To evaluate histopathological alterations triggered by brain death and associated trauma on different solid organs in rats. METHODS: Male Wistar rats (n=37) were anesthetized with isoflurane, intubated and mechanically ventilated. A trepanation was performed and a balloon catheter inserted into intracraninal cavity and rapidly inflated with saline to induce brain death. After induction, rats were monitored for 30, 180, and 360 min for hemodynamic parameters and exsanguinated from abdominal aorta. Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
6
0
6
Order By: Relevance
“…These conclusions are consistent with data from a previously published study 1 . Indeed, lungs are the organs most often considered unsuitable, with only 10-20%…”
Section: Plasmatic Hormonal Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…These conclusions are consistent with data from a previously published study 1 . Indeed, lungs are the organs most often considered unsuitable, with only 10-20%…”
Section: Plasmatic Hormonal Levelssupporting
confidence: 93%
“…Brain death (BD) is a relevant event that causes pathological changes on all the organs [1][2][3] . When used for transplantation marginal organs can influence the survival of the receptor 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that BD induces microcirculatory hypoperfusion and leads to increased local inflammation and organ dysfunction [19]. Pathophysiological changes have been demonstrated in many transplantable organs [20] and might be responsible for the BD-mediated deterioration of organ function [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Em estudos prévios, conduzidos em ratos com morte encefálica, verificou-se aumento na expressão de moléculas de adesão endoteliais na microcirculação mesentérica associada a aumento na migração leucocitária para o tecido perivascular (Simas et al, 2012a;Simas et al, 2012b). A morte encefálica induz hipoperfusão mesentérica relacionada à redução da concentração plasmática de corticosterona endógena, inflamação local e disfunção orgânica (Simas et al, 2012a).…”
Section: Morte Encefálicaunclassified
“…(Prass et al, 2003;Liesz et al, 2009). Além disso, diversos estudos previamente conduzidos em modelo experimental de morte encefálica resultaram em um maior recrutamento de leucócitos em órgãos alvos de transplante, sendo frequentemente observado infiltrado leucocitário no tecido cardíaco, pulmonar, hepático e renal (Simas et al, 2012b;Simas et al, 2015;Yeh et al2002;Faropoulos & Apostolakis et al, 2009;Rostron et al, 2008;Wilhelm et al, 2000b…”
Section: ____________________________________________________________unclassified